2019
DOI: 10.1126/scitranslmed.aat7973
|View full text |Cite
|
Sign up to set email alerts
|

A biologic scaffold–associated type 2 immune microenvironment inhibits tumor formation and synergizes with checkpoint immunotherapy

Abstract: Biomaterials in regenerative medicine are designed to mimic and modulate tissue environments to promote repair. Biologic scaffolds (derived from decellularized tissue extracellular matrix) promote a wound-healing (proregenerative) immune phenotype and are used clinically to treat tissue loss, including in the context of tumor resection. It is unknown whether a biomaterial microenvironment that encourages tissue formation may also promote tumor development. We implanted a urinary bladder matrix (UBM) scaffold, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 40 publications
4
90
0
Order By: Relevance
“…R1 and R2 are distinguished by higher CD11c and lower CD206 expression respectively. These pronounced subset specific profiles elucidate earlier suggestions of complex phenotypes associated with the regenerative UBM microenvironment (25,26).…”
Section: Computational Phenotyping Reveals Limited Inflammatory and Psupporting
confidence: 75%
See 1 more Smart Citation
“…R1 and R2 are distinguished by higher CD11c and lower CD206 expression respectively. These pronounced subset specific profiles elucidate earlier suggestions of complex phenotypes associated with the regenerative UBM microenvironment (25,26).…”
Section: Computational Phenotyping Reveals Limited Inflammatory and Psupporting
confidence: 75%
“…3D). In addition, R2 expressed high levels of Ccl24 (Eotaxin-2), a chemokine for eosinophil attraction that is observed responding to ECM materials (25). Gene set enrichment and gene modules from network analysis also support a unique metabolic profile with expression of Cox5a, Uqcrq, Ndufa1, and Ndufc2 (Fig.…”
Section: Computational Phenotyping Reveals Limited Inflammatory and Pmentioning
confidence: 80%
“…with negative clinical outcomes [30]. In contrary to this traditional scheme of pro-and antitumor microenvironment, a recent study demonstrated that the type 2 immune response characterized by Th2 cells may inhibit tumor formation in melanoma [10]. In line with this research, the Th1, Th2, and the cytotoxic T cell signature prediction test and the demonstration that the radiomic prediction of the Th2 cell signature is feasible in our study are clinically meaningful because these three cells are subsets of influential immune cells in tumor immune responses as mentioned above.…”
Section: Plos Onementioning
confidence: 99%
“…The expression of the programmed death-ligand 1 (PD-L1) gene in the tumor has been associated with a response to checkpoint blockade therapy and prognosis, to some extent [6,7], but the understanding of the complex interactions between tumors and their microenvironment remains insufficient to distinguish between patients who will respond to therapy and those who should be offered alternative treatment. Growing evidence suggests that the efficacy of immunotherapy in cancers is associated with the immune microenvironment of tumors, thereby type 1 and 2 immune responses are believed to be important predictive biomarkers [8][9][10][11]. Generally, type 1 immune responses are thought to be the most relevant to antitumor immunity, and many cancer immunotherapies are designed to augment type 1 immune responses that involve cytotoxic T cells and type 1 helper T (Th1) cells to eliminate tumors [9], whereas a type 2 immune response characterized by type 2 helper T (Th2) cells is often associated with a tumor-permissive environment [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation